The Effect Of Prenatal Yoga On Back Pain In Pregnant Women In The Third Trimester - Meilinda, Vittria; Nurhayati, Nurhayati; Handayani, Sri (Journal of Midwifery and Nursing, 2025)
As pregnancy progresses, physical changes in the mother often lead to various complaints, one of which is back pain. According to data from the Ministry of Health in 2022, approximately 70% of pregnant women experience back pain due to changes in back muscles. This study aims to analyze the effect of prenatal yoga on back pain in pregnant women during the second trimester. The study employed a quasi-experimental design with a pre-test and post-test structure involving a control group. The instrument used to measure pain levels was the Visual Analog Scale. Data collection was conducted from August to September 2024, involving 32 respondents. Data analysis was performed using univariate and bivariate methods, specifically the Wilcoxon and Mann-Whitney tests. The study results showed that the average back pain score before the intervention in the intervention group was 4.75, while in the control group, it was 4.44. After the intervention, the average back pain score in the intervention group decreased to 2.31, whereas the control group only showed a slight decrease to 4.0, with a standard deviation of 0.816. Statistical tests indicated a significant effect of prenatal yoga on back pain in pregnant women during the second trimester (p-value 0.000). In conclusion, prenatal yoga positively impacts reducing back pain in pregnant women during the second trimester. It is recommended that prenatal yoga be widely implemented as an effort to alleviate back pain complaints in pregnant women